2008
DOI: 10.1302/0301-620x.90b12.20681
|View full text |Cite
|
Sign up to set email alerts
|

European validation of the Vancouver classification of periprosthetic proximal femoral fractures

Abstract: The Vancouver classification has been shown by its developers to be a valid and reliable method for categorising the configuration of periprosthetic proximal femoral fractures and for planning their management. We have re-validated this classification system independently using the radiographs of 30 patients with periprosthetic fractures. These were reviewed by six experienced consultant orthopaedic surgeons, six trainee surgeons and six medical students in order to assess intra- and interobserver reliability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 22 publications
4
81
1
4
Order By: Relevance
“…Vancouver C fractures are fractures of the femur distal to the stem. The important weakness of the Vancouver classification is the clinical difficulty in distinguishing between B1 and B2 fractures (5,7,8,21). Lindhal reported a high percentage of periprosthetic failure in type B fractures treated with plate osteosynthesis in his publications fracture; due to the limited mobility expectations of the patient, plate osteosynthesis was chosen.…”
Section: Tab 3: Evaluation Of Treatment Results Based On Thementioning
confidence: 99%
“…Vancouver C fractures are fractures of the femur distal to the stem. The important weakness of the Vancouver classification is the clinical difficulty in distinguishing between B1 and B2 fractures (5,7,8,21). Lindhal reported a high percentage of periprosthetic failure in type B fractures treated with plate osteosynthesis in his publications fracture; due to the limited mobility expectations of the patient, plate osteosynthesis was chosen.…”
Section: Tab 3: Evaluation Of Treatment Results Based On Thementioning
confidence: 99%
“…It has been confirmed to be reliable and valid [4,19]. One must not underscore the importance of verifying stability of the femoral component intraoperatively to properly guide treatment rationale.…”
Section: Discussionmentioning
confidence: 96%
“…Two separate studies have confirmed the reliability and validity of the Vancouver classification system, one by the Vancouver group [4], and another by Rayan et al [19]. In the study by the Vancouver group [4], six observers (three expert attending surgeons and three nonexpert fellow and senior residents) examined 40 radiographs.…”
Section: Validationmentioning
confidence: 93%
See 2 more Smart Citations